Analysis of Sharia Marketing Strategies in Dealing with Business Competition in Semarang Rabbani Store - Ria Resti Ridhawati (Open Access Indonesia Journal of Social Sciences, 2020)
Sharia marketing is spiritual marketing which views competitors as not enemies, but equal partner who are able to spur creativity and innovation of the company. Rabbani Store is one of the first and the largest instant veil company in Indonesia by Issuing a reliable product in the form of an instant veil and other products that have also been developed, namely Muslim Fashion including Kemko, Tunic, Castles and other equipment such as ciput or inner hoods and accessories. Many new business people, the threat of substitute products, which brings new capacity that offers fashion products that are more fashionable. This research is a type of field research using two types of data sources, namely primary data and secondary data obtained using interviews and documentation. After the data is collected, the data is then analyzed using a qualitative descriptive approach. The results of this study state that marketing is carried out by Rabbani store in broad terms in accordance with sharia marketing theory which includes the characteristics of sharia marketing, the principles and practices of Rasulullah’s marketing. And applied in the marketing mix (marketing mix) which consists of four elements, namely the distribution channel (place), products or services (products), price (price) and promotion (promotion). From the analysis of competitive strategies carried out by Rabbani Stores in the face of increasingly, fierce business competition, the business strategy proposed by Michael Porter’s called The Porter’s Competitive Strategic namely differentiation strategy. So that the Rabbani Store when ink was still a leader in Muslim fashion.